Houseal Moves Into Hotter Politics: District 1 Councilman Expects Heavy Scrutinization - Sellers, Richard (Valdosta Daily Times, 1985)
Sellers, Roger. "Houseal Moves Into Hotter Politics: District 1 Councilman Expects Heavy Scrutinization," Valdosta Daily Times, February 17, 1985.
1 electronic record (jpg, jp2, pdf). 1 pages. 1051297 bytes.
Keywords: Valdosta (Ga.); Electronic records; Elections; Politics and government; African Americans; Civil rights